If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 1) + -4(x + -2) = 25 Reorder the terms: 3(1 + 2x) + -4(x + -2) = 25 (1 * 3 + 2x * 3) + -4(x + -2) = 25 (3 + 6x) + -4(x + -2) = 25 Reorder the terms: 3 + 6x + -4(-2 + x) = 25 3 + 6x + (-2 * -4 + x * -4) = 25 3 + 6x + (8 + -4x) = 25 Reorder the terms: 3 + 8 + 6x + -4x = 25 Combine like terms: 3 + 8 = 11 11 + 6x + -4x = 25 Combine like terms: 6x + -4x = 2x 11 + 2x = 25 Solving 11 + 2x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 2x = 25 + -11 Combine like terms: 11 + -11 = 0 0 + 2x = 25 + -11 2x = 25 + -11 Combine like terms: 25 + -11 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| f(x)=-3x^2+15 | | 5*5+7-3= | | 110=w(w+15) | | W^2+15w=110 | | 4xy-4xz= | | t^2-3t=-2 | | 2=16-2p | | 12y^2+y-20=0 | | 1.5x+14=26+0.5x | | 5x+18=12x+4 | | 7w-3(4w+8w)=11 | | 0=-2475+29x^2 | | 6x-3=7+5x | | 1000=-4+2x | | 2(x+39)=3(2x+2) | | 6x+48=8x+40 | | 16x-(4x-1)(4x-1)(4x-3)=29 | | 0=-3x^2+28x+144 | | 36=3w+2 | | 30=x+y+2 | | c-.015c=102 | | x+3/4-x/2=3 | | 0=-x^3+14x^2+144x-7000 | | 6-(v-3)=9(2v+3) | | 7(6x-7)+1=42x | | 10x^2-25x^3=0 | | 8+2n+1= | | x+15=420 | | x^2+14x-150=0 | | 7x=2y-7 | | 6+5(X-5)=2-8(X-5) | | 6+5(X-5)=2-2(X-5) |